Variação genética em Salminus hilarii (Valenciennes, 1849) na região do Alto Rio São Francisco, MG e contribuições para a conservação do grupo - Nunes, Aline Galindo (2010)
The São Francisco river comprises one of the largest and most important river basins of Brazil and one of its main characteristics is the variety of fish species. The genus Salminus (Characiformes: Characidae) constitutes a group of migratory fish with great economic importance in fishing and gastronomy. Within this genus, Salminus hilarii (tabarana), due to its high degree of selectivity for the environment and to occupy the top of the food chain, of great importance to the ecosystem and a good indicator of environmental impacts. Many studies on conservation and population genetics have been conducted using molecular markers such as microsatellites, which can provide data on the genetic processes that are acting in a given population. These markers have relatively conserved flanking sequences, which allows the use of primers that were originally designed for other phylogenetically related species. In this study, nine polymorphic microsatellite loci isolated from Salminus franciscanus were used to assess the genetic variation of S. hilarii collected in three localities in the upper São Francisco river basin, aiming to evaluate the level of genetic variation and identify evidence of population structure, providing support for conservation of this group of fish and contributing effectively to maintain the biodiversity of this ecosystem. The cross amplification results were efficient and were able to identify a relatively high level of genetic variation. Moreover, it was possible to observe the absence of genetic structure between populations, suggesting the occurrence of gene flow between them enough to maintenance of the genetic homogeneity of this populations. These results are important tools, since they can provide information for understanding the behavior and biology of these fish to fisheries management and conservation programs.